Efficacy of single-dose intravitreal dexamethasone implantation for retinal vein occlusion patients with refractory macular edema: A systematic review and meta-analysis - Yuan, Qiongzhen; Gao, Yunxia; Liu, Yilin; Xu, Hanyue; Wang, Tong; Zhang, Ming (Frontiers in Pharmacology, 2022)
Purpose: To assess the functional and anatomical consequences of single-dose dexamethasone (DEX) implants for the treatment of refractory macular edema (ME) secondary to retinal vein occlusion (RVO) after anti-vascular endothelial growth factor agents. Methods: A literature search of studies on switching therapy to DEX implants from anti-VEGF agents in refractory RVO patients was performed with five electronic databases (PubMed, EMBASE, Web of Science, MEDLINE, and Cochrane Library) prior to January 2022. The main outcomes included best-corrected visual acuity (BCVA) and central macular thickness (CMT) changes at different follow-up endpoints from baseline. All analyses were performed using Stata version 15.0. Results: The final analysis included four eligible studies with a total of 99 patients. After single-dose DEX implant application, BCVA improved significantly at 2, 3, and 6 months with an average gain of -0.23 logarithm of the minimum angle of resolution (logMAR) (p=0.004), -0.20 logMAR (p=0.027), and -0.09 logMAR (p=0.021). Mean CMT reduction was also significant from baseline to 2 months (-241.89 μm, p<0.001), 3 months (-222.61 μm, p<0.001), and 6 months (-90.49 μm, p<0.001). No serious adverse events were observed in any of the included studies. Conclusion: This meta-analysis showed that RVO patients with refractory ME could benefit significantly from switching therapy to DEX implantation, with an efficacy lasting 6 months after a single-dose application. Intravitreal DEX implantation is a safe and effective option for refractory cases.